Systematic Mapping Study: Change Management in Family Business - Raja Ainaya Alfatiha; Sam'un Raharja; Asmaul Husna (Bahtera Inovasi, 2023)
Family business is a legacy business that was pioneered and managed with the family, maintaining a family business is easy especially to survive and continue for generations. In this case, to be able to achieve business continuity, family companies need to make changes. Changes in management are one way to maintain the continuity of the family business. So this study aims to map the topic of change management analysis (change management) in family companies using the Systematic Mapping Study (SMS) to see the development of research. Search data using the Scopus database and science direct with the results of 29 articles. Based on the mapping, it shows that the most highly discussed research focuses are corporate governance, entrepreneurship, corporate capability, and organizational development. The research method that is widely used is qualitative, namely 20 articles (69.0%). The dominant type of paper used is the evaluation research category, which is 14 articles (48.3%). The publication trend of countries that do a lot of research is Italy, which is 4 articles (13.8%) and the peak of publication is in 2021 with 7 articles (24.1%)